SEPARATE PROBLEMS OF COUNTERCURRENCY IN THE ECONOMIC PROCESS - Khlivnyi, Khlivnyi (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to outline the problems of implementation of measures of counter-enforcement of the claim in the economic process, based on the analysis of which to propose ways to solve and improve the economic procedural legislation regarding the provision of the claim. Research methods: the method of analysis is applied to research the positions of lawyers and identify problems of securing a claim. The formal-logical method was used to form conclusions, proposals aimed at solving the identified problems and improving economic procedural legislation regarding the provision of a claim and counter-enforcement in particular. Results: it has been proven that the institution of counter-security is aimed at protecting the defendant’s rights; the practical application of the requirement regarding the offer of counter-security is mostly of a formal nature and may be rejected by the court on condition of the applicant’s request not to apply such a measure; it is proposed to change the approach formed by judicial practice and to enshrine the legal counter-security as mandatory, without the possibility of its cancellation; the defendant has the duty to show the connection between the applied measures to ensure the claim and the damage caused and to substantiate the amount of the damage caused. Discussion: singling out separate grounds for the application of counter-security will violate the balance of equality of the parties to the case, therefore, counter-security should be applicable to all types of measures to secure a claim in an economic process. It is worth paying attention to the fact that, in addition to those specified in the law, there are other grounds for canceling measures to secure a claim, which are not directly defined by procedural legislation. The absence in the application of measures to ensure the offer of counter-security is grounds for the return of the application, and the closing of the proceedings, the satisfaction of the claim or the applicant’s failure to provide evidence regarding the provision of counter-security are grounds for canceling the decision on securing the claim and the resolution on counter-security. The position of the Supreme Court is debatable, that the counter-security in the form of compensation for potential damage is of an advisory nature, so the presence or absence of an offer must be considered by the court in a specific case.